PLANNING AND ORGANIZATION OF WORK OF THE EXTRACURRICULAR EDUCATIONAL INSTITUTION AS A SOCIO-PEDAGOGICAL ISSUE AND THE BASIS OF DEVELOPMENT OF A CREATIVE PERSONALITY - Razmolodchykova I. V. (International Journal of Innovative Technologies in Social Science, 2022)
The article highlights the approaches to the study of planning and organization of out-of-school educational institution, which today is an important scientific issue and a necessary condition for the formation and development of a creative personality. Based on the analysis of the structure and content of planning the work of an out-of-school educational institution, the components and priority areas are presented, in which relation the educational policy of the institution is implemented. The theoretical bases of planning the work of an out-of-school institution are indicated. The requirements of the society to the development and upbringing of an individual in the work of an out-of-school educational institution are substantiated. The directions of work and functions which will promote successful realization of the programs directed on development of a creative personality of the child are defined.